Pengembangan Komposter Sampah Rumah Tangga Untuk Mendukung Lingkungan Berkelanjutan Di Dusun Klitih Desa Wajik Kecamatan Lamongan Kabupaten Lamongan - Heru Apriliyanto; Muhammad Kurnia Sandi; Wildan Alfikrul Karim; Wulan Cahya Ningrum; Muhammad Roziqi Yogatama; Muhammad Faiq; Wiharyanti Nurlailiyah (Universitas Muhammadiyah Gresik, 2023)
Household waste is anything that is no longer used, used, liked, so it must be disposed of. The majority of people think that household waste is something that has no value and is not utilized. In Klitih Hamlet there are 80 heads of households, where each house can produce around 0.5 to 1 kilogram of household waste per day. Abundant and unutilized waste can cause air pollution, attract lots of flies, as well as an unsightly environment. Therefore, it must be handled immediately by managing household waste as a material for making compost which produces solid organic fertilizer and liquid organic fertilizer, while inorganic household waste is used as a medium for making verticulture. The stages of implementing this program began with preparation, then socialization was held to PKK Dusun Klitih women. The second stage was the distribution of Tooster packages to 43 PKK women. The third stage is composting monitoring. After that, making verticulture media and planting. The fourth stage is verticulture monitoring and verticulture assessment. The fifth stage was harvesting verticulture vegetables and compost and followed by filling out questionnaires by PKK women. The fifth stage is closing by holding talk shows and joint gymnastics, then evaluating activities. The last stage is the preparation of progress reports and the preparation of final reports and seminars. The results of the implementation are the existence of new habits from PKK Dusun Klitih women for program sustainability in utilizing organic and inorganic household waste so that it has economic value by producing compost products, liquid organic fertilizer, and plants from verticulture system cultivation.